Analysis of not Using the Multi-Year Contract Method in Directorate General of Islamic Education - Effendi, Edy; Zunaidi, Achmad (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2020)
The application of multi-year budgeting is the implementation of the medium-term expenditure framework approach. Furthermore, the multi-year budgeting is carried out through the procurement of goods and services called the Multi-Year Contract. Multi-year budgeting provides certainty for the continued funding of activities/projects. Although, an activity/project that naturally lasts more than one fiscal year but not all planners use multi-year budgeting. This study reveals the background behind the policy of not using the multi-year budgeting method by spending unit in the Directorate General of Islamic Education, Ministry of Religion. The method used in this study uses quantitative research using the Analytical Hierarchy Process (AHP) model. The results of the study indicate that the existence of laws and regulations regarding multi-year budgeting is the most important element as the main reason as the choice of multi-year budgeting compared with internal factors. The most important element of legislation is related to the absence or unclear rules. Meanwhile, the most important element of internal factors is the certainty of funding activities/projects.